Description of the immature stadia of Balacha melanocephala (Insecta: Hemiptera: Cicadellidae: Cicadellini) with biological notes - Quintas, Victor; Prando, Jádila S.; Alasmar, Luísa; Domahovski, Alexandre C.; Timóteo, Ágatha; Mejdalani, Gabriel (Zootaxa, 2026)
Balacha Melichar, 1926 (Cicadellinae) comprises 10 species and is distributed across southeastern and southern Brazil, Uruguay, Paraguay, and Argentina. Here we provide the first detailed descriptions and illustrations of the five nymphal stadia of B. melanocephala (Signoret, 1854), type species of the genus, based on specimens collected on Eryngium (Apiaceae) in the municipality of São José dos Pinhais, state of Paraná, southern Brazil. Biological notes on nymphs and adults are also given. For determining the nymphal stadia of B. melanocephala, a reliable criterion is a combination of body size and wing pad development, comparing the relative extension of wing pads in relation to the abdominal segments. Our field observations suggest that the predominantly yellow coloration of the nymphs of this species may represent an adaptive trait that enhances camouflage on the young inner leaves of Eryngium plants.